Telomere attrition and dysfunction: a potential trigger of the progeroid phenotype in nijmegen breakage syndrome - Habib, Raneem; Kim, Ryong; Neitzel, Heidemarie; Demuth, Ilja; Chrzanowska, Krystyna; Seemanova, Eva; Faber, Renaldo; Digweed, Martin; Voss, Reinhard; Jäger, Kathrin; Sperling, Karl; Walter, Michael (Aging, 2020)
BACKGROUND: Nibrin, as part of the NBN/MRE11/RAD50 complex, is mutated in Nijmegen breakage syndrome (NBS), which leads to impaired DNA damage response and lymphoid malignancy. RESULTS: Telomere length (TL) was markedly reduced in homozygous patients (and comparably so in all chromosomes) by ~40% (qPCR) and was slightly reduced in NBS heterozygotes older than 30 years (~25% in qPCR), in accordance with the respective cancer rates. Humanized cancer-free NBS mice had normal TL. Telomere elongation was inducible by telomerase and/or alternative telomere lengthening but was associated with abnormal expression of telomeric genes involved in aging and/or cell growth. Lymphoblastoid cells from NBS patients with long survival times (>12 years) displayed the shortest telomeres and low caspase 7 activity. CONCLUSIONS: NBS is a secondary telomeropathy. The two-edged sword of telomere attrition enhances the cancer-prone situation in NBS but can also lead to a relatively stable cellular phenotype in tumor survivors. Results suggest a modular model for progeroid syndromes with abnormal expression of telomeric genes as a molecular basis. METHODS: We studied TL and function in 38 homozygous individuals, 27 heterozygotes, one homozygous fetus, six NBS lymphoblastoid cell lines, and humanized NBS mice, all with the same founder NBN mutation: c.657_661del5.
Keywords: Young Adult; alternative lengthening of telomeres; modely nemocí na zvířatech; telomere-position effect over long distances; heterozygot; Male; homozygot; Child, Preschool; telomerasa; Progeria; karyotypizace; Cell Line, Tumor; Heterozygote; mladý dospělý; Adolescent; syndrom Nijmegen breakage; Infant; Child; Karyotyping; dítě; DNA repair; nibrin; jaderné proteiny; mužské pohlaví; Homozygote; Telomere Homeostasis; mladiství; proteiny buněčného cyklu; předškolní dítě; Nijmegen Breakage Syndrome; Animals; lidé; Telomerase; ženské pohlaví; myši transgenní; nijmegen breakage syndrome; Humans; telomery; zvířata; kojenec; progerie; Disease Models, Animal; myši; homeostáza telomer; nádorové buněčné linie; Mice; Female; Cell Cycle Proteins; Nuclear Proteins; Mice, Transgenic; Telomere